2019
DOI: 10.1186/s12986-019-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whey protein hydrolysate ingestion on post-exercise muscle protein synthesis compared with intact whey protein in rats

Abstract: BackgroundIt is well known that ingestion of protein sources can stimulate muscle protein synthesis (MPS). The intake of whey protein is highly effective especially for accelerating MPS. Whey protein hydrolysate (WPH) can raise postprandial plasma concentration of amino acids, which impact stimulation of MPS more rapidly and highly than intact whey protein. However, it is unclear which is more effective for stimulating MPS, WPH or intact whey protein. The aim of the present study was to compare the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Specifically, following a 2-h swimming protocol, MPS 60 min following ingestion of the whey protein hydrolysate was significantly higher compared with a control intact whey protein. Interestingly, the whey protein hydrolysate caused greater MPS and phosphorylated 4E-binding protein 1 (4E-BP1) levels compared with the control whey protein only at the lower dose (i.e., 0.5 g·kg −1 ·day −1 ) [ 129 ], which supports the notion that whey protein hydrolysates may be more efficacious under conditions of suboptimal protein intakes and in relative proximity of exercise, albeit in rodents. Similar findings have been also observed with anabolic signaling markers and the attenuation of muscle loss with whey hydrolysates compared with its constituent AAs and/or non-hydrolysed forms [ 130 132 ].…”
Section: Skeletal Muscle Anabolism and Exercise-induced Adaptation And Recoverymentioning
confidence: 83%
See 1 more Smart Citation
“…Specifically, following a 2-h swimming protocol, MPS 60 min following ingestion of the whey protein hydrolysate was significantly higher compared with a control intact whey protein. Interestingly, the whey protein hydrolysate caused greater MPS and phosphorylated 4E-binding protein 1 (4E-BP1) levels compared with the control whey protein only at the lower dose (i.e., 0.5 g·kg −1 ·day −1 ) [ 129 ], which supports the notion that whey protein hydrolysates may be more efficacious under conditions of suboptimal protein intakes and in relative proximity of exercise, albeit in rodents. Similar findings have been also observed with anabolic signaling markers and the attenuation of muscle loss with whey hydrolysates compared with its constituent AAs and/or non-hydrolysed forms [ 130 132 ].…”
Section: Skeletal Muscle Anabolism and Exercise-induced Adaptation And Recoverymentioning
confidence: 83%
“…A recent study using a rodent model investigating the effects of whey protein hydrolysate (0.5 and 2.0 g·kg −1 ·day −1 ) compared with an intact whey protein on postexercise MPS has produced interesting findings with regards to the muscle anabolic potential of hydrolysates [ 129 ]. Specifically, following a 2-h swimming protocol, MPS 60 min following ingestion of the whey protein hydrolysate was significantly higher compared with a control intact whey protein.…”
Section: Skeletal Muscle Anabolism and Exercise-induced Adaptation And Recoverymentioning
confidence: 99%
“…Furthermore, independently of absorption kinetics, hydrolyzed protein may have beneficial physiological effects. In a study with rats, it was shown that hydrolyzed whey protein stimulated MPS more efficiently than intact whey protein, even though lower aminoacidemia was observed after ingestion of the hydrolysate [40]. This finding is possibly related to a higher plasma insulin concentration observed after ingestion of the whey protein hydrolysate compared to the intact whey protein, since insulin may support MPS when the AA availability is sufficient [41].…”
Section: Discussionmentioning
confidence: 98%
“…The enzymatic hydrolysis of proteins is an effective method widely used to produce bioactive peptides with multifunctional properties (Panyam and Kilara, 1996). In the case of whey protein (Nakayama et al, 2019), protein hydrolysate has been reported to stimulate muscle protein synthesis more effectively than the original protein. Alcalase and Flavourzyme have been mostly used to hydrolyse different plant proteins, such as rice or soy protein, to produce bioactive peptides (Ahmadifard et al, 2016;Gomes and Kurozawa, 2020).…”
Section: Introductionmentioning
confidence: 99%